RETRACTED: Building a sustainable future: how intelligent automation Is transforming higher education's sustainability efforts - Moşteanu Narcisa Roxana (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001